Effect of channa striatus on inflammatory markers as an adjunt treatment in allergic rhinitis-a randomized double-blinded study - Abu Bakar, Muhammad Nasri (2015)
Introduction: Channa striatus (snakehead fish) have been shown to have antiinflammatory and anti-nociceptive properties. This study aimed to discover the effect of its anti-inflammatory property on the inflammatory process in allergic rhinitis. Objective(s): To determine the effect of Channa striatus extract on patients’ allergic rhinitis inflammatory markers, namely eosinophil and interleukin-4 level and their Total Nasal Symptoms Score. Methodology: A 6 weeks, randomized double-blinded placebo-controlled trial, parallel group comparative clinical study. Forty six allergic rhinitis patients were randomized to receive Channa striatus extract capsules or placebos for 6 weeks. Patients were assessed clinically at weeks 0, 2 and 6. Blood for serum eosinophil and interleukin-4 were taken at initial and final visit and the results were compared. Results: The result showed significant decrement of serum eosinophil level in Channa striatus group (p<0.05) however the comparative analysis of the mean difference between two groups was not statistically significant. The result for interleukin-4 level showed no statistically significant changes in either group. The Total Nasal Symptoms Score reduction in both group are significant and comparative analysis of the mean difference between two groups was statistically significant for those with moderate and severe symptoms. Conclusion: Even though Channa striatus showed nonsignificant additional immunomodulation effects in laboratory analysis, however its role as an adjunct treatment in allergic rhinitis did show significant reduction in TNSS for patients with moderate and severe symptoms.